MANAJEMEN MASJID AL-HUDA DI DESA ALIAGA UJUNG BATU LIMA - Muhammad Ronaydi (Yonetim Jurnal, 2023)
This article discusses the Al-Huda Mosque which is located in Aliaga Ujung Batu Lima village, precisely located in North Sumatra Province. This research uses qualitative methods with netnography techniques. The results of this research are that the Al-Huda Mosque has several functions, apart from prostrating to its Lord, namely first, as a place of unity and increasing Islamic brotherhood. Second, as a place for the educational process. Third, of course as a platform for preaching. Fourth, a means for the benefit of the people. Fifth, a place for deliberation and exchanging ideas. Apart from the function of the Al-huda Mosque, this mosque also has activities that can maintain the functions listed, including the prayer activities five times a day and night, the Fardhu Friday prayer activities, as well as congregational prayers for Eid al-Fitr and Eid al-Adha. There are also educational activities such as reciting the Koran every afternoon, book learning, including fiqh, tauhid and tajwid, there is also a training process for fahmil and the art of Qiro'ah. And the next activities are of course related to the benefit of the people, such as conducting recitations, providing compensation and activities carried out for the benefit of the people.